IOT Lecture: Institute of theology lectures - Alston, Wallace M. (I.O.T. Lecture, 2005)
[1.] Is the church in trouble? --[2.] The church as a theological community --[3.] The pastor as theologian --[4.] Pastoral task as theological occasion.